POLA KOMUNIKASI PEMIMPIN DALAM MENINGKATKAN MOTIVASI KERJA KARYAWAN DIVISI MARKETING CV. MEDIA AGUNG SURAKARTA - Nugroho, Adi; Wangi, Maya Sekar; Siswanta, Siswanta (Solidaritas, 2024)
ABSTRACT Good and proper communication patterns are essential for a leader. In this regard, cooperation will proceed smoothly. The communication conducted by a leader should take the form of instructions or input, such as suggestions, commands, advice, or constructive criticism. Frequent miscommunication between leaders and subordinates can affect employee motivation. The purpose of this research is to determine the communication patterns applied by leaders in enhancing employee motivation in the Marketing Division of CV Media Agung Surakarta. This research is of a descriptive qualitative nature. The data collection techniques in this research include observation, internal company data, journals, and literature studies. Data analysis is conducted using the Miles and Huberman Interactive model. The data analysis process is carried out in several stages, namely data condensation, data presentation, and drawing conclusions or verification. The results of this research indicate that in the Marketing Division of CV. Media Agung Surakarta, a chain communication pattern is used. Additionally, there are obstacles such as miscommunication between the leader and field staff in carrying out their tasks, which affects employee motivation. Keywords: Communication Patterns, Leadership, and Work Motivation